(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Rita Dove, though belonging to the narrow limitations of African American literature, is a poet who achieved great praise and international appreciation for her works. she stresses in her works the concept of black identity. The works have their own uniqueness and creative touch that highlights the quest for identity in Rita Dove. It is in fact, her spontaneity and apt informative content with which history and culture are being glorified at the outset. Dove wishes to bring out and expose to the world about the difficulties faced by black literature amidst American culture. The traumatic lives of black slaves in America are also portrayed by Dove in a vivid manner. The slaves have been deprived of their rights and even their voice has been curbed and were treated very badly. It was Dove who in her works has pulled out from the grave the agony and torture of the black people by means of her poetry.